Year over year comparison of sediment quality in the rivers of Eastern Slovakia - Singovszka, Eva; Balintova, Magdalena (Scientific Review Engineering and Environmental Sciences (SREES), 2020)
Quality is one of the most important risk indicators in river basins. Therefore, monitoring and evaluating water and sediment quality has a very important role in process of risk management. The aim of the monitoring is provide for the sustainability of water bodies and these results are the basis for the risk management in the river catchment area. Hornad, Laborec and Poprad are the rivers in Eastern Slovakia. Hornad and Laborec belongs to basin of Danube and Poprad belongs to basin of Vistula. Sediment sampling was carried out according to ISO 5667-6. Monitoring was carried out in the spring on 2017–2018. The chemical composition of sediments was determined by means of X-ray fluorescence (XRF) using SPECTRO iQ II (Ametek, Germany, 2000). The results of sediment quality evaluated by method PERI revealed that the quality of sediment in 2018 was better than 2017. Results of XRF analysis of sediments were compared with the limited values according to the Slovak Act 188/2003 Coll. of Laws on the application of treated sludge and bottom sediments to fields. It can be state that limit values comparing with Slovak legislation were not exceeding in all sediment samples in rivers in Eastern Slovakia. Based on the monitoring data of sediment quality in the study area, a quantitative analysis of heavy-metal pollution in sediment was conducted using the method of potential ecological risk index (PERI) which is method for evaluate the potential ecological risk of heavy metals. It is based exclusively on chemical parameters of sediments because sediment data show mean integrated values in time, with higher stability than water column parameters; sediments are easily sampled at field work; sediment samples are more representative for time and space scales and analytical data are easily obtained, especially because sediments present high concentrations of contaminants, decreasing the possible errors due to detection limits of the applied analytical method. This method comprehensively considers the synergy, toxic level, concentration of the heavy metals and ecological sensitivity of heavy metals. Potential ecological risk index can be obtained using three basic modules: degree of contamination (CD), toxic-response factor (TR) and potential ecological risk factor (ER). The results show on the basis on potential ecological risk index that the quality of sediment in 2018 is better than 2017. The worst result shows Hornad in 2017. Significant improvement occurred at the sampling point S2 in Hornad in 2018. The best results show Laborec in 2018. The results show on the basis on potential ecological risk index that quality of sediment in 2018 is better than 2017.